Shift current photovoltaic effect in a ferroelectric charge-transfer complex - M. Nakamura; S. Horiuchi; F. Kagawa; N. Ogawa; T. Kurumaji; Y. Tokura; M. Kawasaki (Nature Communications, 2017)
The bulk photovoltaics refers to an effect whereby electrons move directionally in non-centrosymmetric crystals upon light radiation. Here, Nakamura et al. observe this effect in a ferroelectric organic charge-transfer complex, which shows large diffusion distance of photogenerated electrons over 200 µm.